Chromium Propionate Enhances Adipogenic Differentiation of Bovine Intramuscular Adipocytes - Tokach, Rebecca J.; Ribeiro, Flavio R. B.; Chung, Ki Yong; Rounds, Whitney; Johnson, Bradley J. (Frontiers in Veterinary Science, 2015)
In vitro experiments were performed to determine the effects of increasing concentrations of chromium propionate on mRNA and protein abundance of different enzymes and receptors. Intramuscular and subcutaneous preadipocytes and bovine satellite cells were isolated from the longissimus muscle to determine the effect of treatment on glucose transporter type 4 (GLUT4) and peroxisome proliferator-activated receptor γ mRNA and GLUT4 protein abundance. Preadipocyte cultures were treated with differentiation media plus either sodium propionate or different concentrations of chromium propionate (CrPro) for 96, 120, and 144 h before harvest. This study indicated adipogenesis of the bovine intramuscular adipocytes were more sensitive to the treatment of chromium propionate as compared to subcutaneous adipocytes. Enhancement of adenosine monophosphate-activated protein kinase and GLUT4 mRNA by CrPro treatment may enhance glucose uptake in intramuscular adipocytes. Chromium propionate decreased GLUT4 protein levels in muscle cell cultures suggesting those cells have increased efficiency of glucose uptake due to exposure to increased levels of CrPro. In contrast, each of the two adipogenic lines had opposing responses to the CrPro. It appeared that CrPro had the most stimulative effect of GLUT4 response in the intramuscular adipocytes as compared to subcutaneous adipocytes. These findings indicated opportunities to potentially augment marbling in beef cattle fed chromium propionate during the finishing phase.